Immigrant integration in ITI/SUD strategies: The case of Athens, Greece - Nikos Karadimitriou; Thomas Maloutas (European Journal of Spatial Development, 2023)
Foreign immigration from low-income countries to the Athens Functional Urban Area (FUA), started in earnest in the early 1990s. However, the first integrated territorial development instrument which covers immigrant integration (the Integrated Territorial Investments- ITI), was introduced in the mid-2010s as a result of adopting relevant EU Regulations.